Anticipatory adaptation and the role of decadal climate information in rural African livelihood systems: Lessons from the Mid-Zambezi Valley, Zimbabwe. Issue 2 (21st March 2016) - Nyamwanza, Admire M.; New, Mark
Abstract : Purpose: – This study aims to explore the utility of anticipatory adaptation to climate variability and related livelihood sensitivities in rural African contexts using the case of Mbire district situated in the mid-Zambezi valley region of Zimbabwe. The provision of decadal climate information (up to ten years), as part of an anticipatory adaptation package, is at the centre of analysis. Design/methodology/approach: – The study used semi-structured and key informant interviews, with a total of 45 semi-structured interviews being conducted with randomly selected long-term communal farmers in the case study area. Whilst data from semi-structured interviews was arranged in Microsoft Excel, thematic analysis was used in analyzing all data. Findings: – Anticipatory adaptation and decadal climate projections are shown to potentially enhance flexibility in adaptation planning vis- à-vis responding to climate variability and other challenges, as well as reduce chances of maladaptation in responding to climate challenges in the context of multiple and reinforcing stresses and shocks. Originality/value: – Anticipatory adaptation, with its three main pillars of future analysis, flexibility of strategies and proactive action, is emerging as key in assisting adaptation planning, the harnessing of opportunities and decision-making vis- à-vis responding to climate uncertainties and related livelihood sensitivities. Yet there have not been much empirically grounded analyses in understanding the role of anticipatory adaptation in rural Africa. This study therefore adds to evidence-based analyses towards understanding the role and utility of anticipatory adaptation in local communities in Africa.